1968
DOI: 10.3758/bf03212730
|View full text |Cite
|
Sign up to set email alerts
|

Visual orientation during and after lateral head, body, and trunk tilt

Abstract: Visual judgments of orientation were investigated during (effect) and after (aftereffect)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
40
2

Year Published

1968
1968
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 29 publications
5
40
2
Order By: Relevance
“…First, when S is tilted laterally to the recumbent position, there is relatively little change in the apparent orientation of a figure in a dark field (Wade, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…First, when S is tilted laterally to the recumbent position, there is relatively little change in the apparent orientation of a figure in a dark field (Wade, 1968).…”
Section: Discussionmentioning
confidence: 99%
“…However, when the tilt is restricted to the head, results vary from one experiment to another. They are E effects (Day & Wade, 1969;Wade, 1968Wade, , 1969Witkin & Asch, 1948a), A effects (Dichgans, Diener, & Brandt, 1974;Parker, Poston, & Gulledge, 1983), or occasionally no general effect (DiLorenzo & Rock, 1982;Merker & Held, 1981).…”
Section: Aubert and Miiller Effectsmentioning
confidence: 99%
“…Much evidence (e.g., Ebenholtz, 1977;Howard & Templeton, 1966;Schone & Lechner-Steinleitner, 1978;Wade, 1968Wade, , 1970Wade & Day, 1968;Yardley, 1990) has indicated that when we tilt our head (or body) 45°or more to one side in the frontal plane, a visual line that is parallel to gravity is perceived as tilting to the opposite direction of the head tilt (the A effect); whereas, with a head tilt of less than 45°, the visual line is perceived as tilting in the same direction as the head tilt (the E effect). When the head is slanted back-ward in the median plane, the gaze direction judged as straight ahead is higher than that obtained before backward slanting (Shebilske & Fogelgren, 1977;Shebilske & Karmiohl, 1978).…”
mentioning
confidence: 99%